Lajur Ampuh Membaca Bahasa Melayu(LAMBM) In The Teaching and Learning Process - Subramaniam, Vijayaletchumy; Shuhada, Nadia; Shazreena, Amirra (Advances in Social Sciences Research Journal, 2019)
Lajur Ampuh Membaca Bahasa Melayu(LAMBM) is an innovative teaching aid (ABM) for the basic learning in Malay Language created and produced to help Malay Language teachers to solve the problem of the inability to read in Malay Language among students. The implementation and formation of this process adopt the Research of Design and Development approach (DDR), QAIT Model by Slavin (1994) and ARCS Motivation Model by Keller (1988). This syllable basic learning approach employs five learning techniques in the form of games as the teaching aid, namely sound segment, syllable cards, syllable column basic board, syllable consolidation table and syllable poster. Every teaching aid has reading mastery levels starting from introduction to consonants and vowels, pronunciation of letter sounds, reading basic syllables, forming the combination of two syllables, syllable recovery, syllables consolidation and syllables enrichment. LAMBM has undergone a trial segmentt of 4 schools and obtained positive feedback from teachers. The test result at school also shows that LAMBM can engage students to read in Malay Language easily. With LAMBM approach in teaching and learning in class, weak students are able to involve themselves actively in the games while strengthening their mastery of syllable to further increase reading skills. LAMBM has a wide market size in and outside the country. The use of LAMBM increases students’ individual and group participation. LAMBM can also engage weak students to take part actively in class activities. Thus, use of LAMBM in schools demonstrates innovative initiative in the 21st century teaching and learning.